2009
DOI: 10.1063/1.3216836
|View full text |Cite
|
Sign up to set email alerts
|

Surface scattering effect on the electrical resistivity of single crystalline silver nanowires self-assembled on vicinal Si (001)

Abstract: Fundamental questions as to the nature of electron surface scattering in nanoscale materials remain unanswered. In order to isolate the effects of surface scattering from grain boundary scattering, single crystalline trapezoidal silver (Ag) nanowires were self-assembled on vicinal silicon substrate. The well established kinetic theory to model electron surface scattering effects on the electrical resistivity of nanowires was extended to include trapezoidal geometries. The experimentally measured electrical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
4
26
1
Order By: Relevance
“…This value is quite close to that of bulk silver (15.9 nΩ.m), and is consistent with values previously measured by Huang et al for single crystal Ag nanowires. 36 No dependence of the resistivity on nanowire diameter was observed for the nanowires measured -see Supporting Information for more information. This resistivity value was then used to estimate R1 and R2, and to extract values for Rjxn.…”
Section: Measuring the Junction Resistancementioning
confidence: 99%
“…This value is quite close to that of bulk silver (15.9 nΩ.m), and is consistent with values previously measured by Huang et al for single crystal Ag nanowires. 36 No dependence of the resistivity on nanowire diameter was observed for the nanowires measured -see Supporting Information for more information. This resistivity value was then used to estimate R1 and R2, and to extract values for Rjxn.…”
Section: Measuring the Junction Resistancementioning
confidence: 99%
“…Lattice fringes with spacing of 0.2046 nm which are also observed corresponds to the (200) planes in FCC crystalline silver. It can be seen that the silver coating layer is nano-crystallized without any amorphous structure [15]. …”
Section: Resultsmentioning
confidence: 99%
“…In a publication by Huang et al 18 it was shown that the electrical resistivity of a single crystalline trapezoidal AgNW is dominated by the electron diffusely scattering on the nanowire surface and explained their experimental results using Chamber's approach 19 to the Fuchs and Sondheimer theory. 20,21 Their work was focused to differentiate the sur- face scattering from the grain boundary scattering and for single crystal wires the experimental resistivity fits well to the theoretical resistivity models that are close to purely diffuse surface scattering.…”
Section: Resultsmentioning
confidence: 99%